2005
DOI: 10.2320/matertrans.46.2968
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trace Additions of Ag on Precipitation in Al–Mg Alloys

Abstract: Effect of Ag additions on the precipitate microstructures of the Al-10Mg alloys has been investigated using transmission electron microscopy (TEM) and electron diffraction.In the Al-10Mg alloy aged at 240 C, age-hardening response is attributable initially to an array of coarse-scale, sparsely distributed rodlike and/or plate-like 0 precipitate (particles). At the maximum hardness, the microstructure contained an increased volume fraction of coarsescale 0 and precipitate particles. In a well over-aged conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…0.5 h) 17) as well as the present microstructural observations for the Al-10 mass%Mg alloy aged at 200 C (e.g. 1, 2 and 4 h) in Figs.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…0.5 h) 17) as well as the present microstructural observations for the Al-10 mass%Mg alloy aged at 200 C (e.g. 1, 2 and 4 h) in Figs.…”
Section: Discussionmentioning
confidence: 83%
“…2(a)) is indexed for a ½11 2 26 direction of a hexagonal structure, and suggests to be a metastable 0 phase. The previous paper revealed the formation of a precipitate cluster consisting of three distinguishable parts, such as blocky, irregularly-shaped and lath-like in the Al-10 mass%Mg alloy aged 5 h at 240 C. 17) These heat treatments again correspond to under-ageing conditions. 15) Another example from the microstructure of the binary alloy, aged 5 h at 240 C, is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, some researchers have studied the aging process in Al-Mg-Ag alloys and found that the addition of Ag has a marked impact on the precipitation particles. The hardness of the alloy was improved conspicuously using only small amounts of Ag [15,16]. However, these researchers mainly focused on 5xxx series aluminum alloys, which contained over 10 wt.% Mg.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some research has reported that Ag played a positive role on aging hardening of an aluminum alloy [ 10 , 11 ]. For 5xxx aluminum alloys, the influence of Ag is mainly focused on the high-Mg content (>10 wt.%) Al-Mg alloys [ 12 , 13 ]. Due to the poor corrosion resistance and inferior processability, the application of high-Mg content Al-Mg alloys was limited.…”
Section: Introductionmentioning
confidence: 99%